A virtual dynamic model of laser material processing - Maung Maung Zaw Min. (2008)
The objective of the project is to build a 3D model of material processing using a laser source, which represents the weld pool behaviour with acceptable accuracy. Mathematical models, such as weld penetration depth and weld pool model will also be used to graphically describe the geometrical features of the material, such as the depth and the width of weld pool, under laser processing. The virtual model will be responsive to input parameters, for example laser power and laser scanning speed, as well as be able to link up to other components in the process through its output parameters, which are the weld pool profiles of the material.